GEOLOGI DAN MODEL KOLABORASI PENGEMBANGAN GEOPARK IJEN, DI KABUPATEN BANYUWANGI - Rohaendi, Nendi; Setiawan, Iwan Fahlevi; Budiyono, Arif; Harmoko, Alex Antonius; Wahyudi, Wahyudi (PPSDM Geominerba, 2023)
The Banyuwangi area has special features in terms of geology and mineralization, this is proven by the designation as an Ijen geopark and the existence of a mining company. The purpose of writing this article is to describe the potential of the Ijen geopark in developing geotourism in the Banyuwangi area. Geoparks are understood as a combination of geological diversity, biodiversity and cultural diversity. Geopark management is managed for conservation, education and economic purposes in a sustainable manner, with active involvement from the community and local government, so that it can be used to increase people's understanding and concern for the earth and its surrounding environment. The result of this writing is a general description of the geotourism potential in the Banyuwangi area and its economic development.